Experiment Driven Co-Simulation Model of Wheel Loader Attachment Hydraulics System for Influence Assessment of Hydraulic Accumulator Parameters on Energy Recuperation Efficiency - Cezary Rudzki; Adam Bartnicki; Arkadiusz Rubiec; Tomasz Muszyński; Mirosław Przybysz (Energies)
The following paper describes research on the influence of hydraulic accumulator parameters on the efficiency of energy recovery for a simulation model of a wheel loader using the results of experimental research. A design solution for the energy recovery system for the loader attachment was presented, which allows for the recovery of the potential energy of the boom, bucket, and load. The presented simulation model was developed based on a real object. The necessary operating parameters were determined using experimental tests. The study used the co-simulation method of mechanical and hydraulic models in order to more accurately reflect the actual behavior of the research object. The validated simulation model was extended with the developed energy recovery module based on a hydraulic accumulator. The results of the conducted tests have indicated the influence of hydraulic accumulator parameters on the efficiency of energy recovery and potential directions for further research.